Brain sex-dependent alterations after prolonged high fat diet exposure in mice - Valentina Murtaj; Silvia Penati; Sara Belloli; Maria Foti; Angela Coliva; Angela Papagna; Cecilia Gotti; Elisa Toninelli; Remy Chiaffarelli; Stefano Mantero; Susanna Pucci; Michela Matteoli; et al. (Communications Biology, 2022)
Analysis of male and female mice exposed to a high fat diet reveals that the male mouse brain is more susceptible to resultant metabolic changes.